Pemahaman Perawat Terhadap Dasar Hukum dan Tanggung Jawab Pelimpahan Wewenang Tindakan Medis di IGD - Mike Asmaria; Hilma Yessi; Debby Silvia Dewi (Universitas Pahlawan Tuanku Tambusai, 2026)
Delegating authority from doctors to nurses is a common practice in emergency services in the Emergency Department (ER) to expedite patient care and improve service effectiveness, particularly in emergency situations or when there are limited medical personnel. However, its implementation still faces various obstacles related to legal aspects, namely the legal basis, professional accountability, and legal protection for the health workers who carry it out. Therefore, it is necessary to conduct research on understanding the delegation of authority in the Emergency Department of Prof. M. Yamin Pariaman Regional Hospital. The methodology used is a qualitative, descriptive-analytical approach by conducting intensive interviews with seven nurses working in the ER. The findings of this study revealed that most nurses still do not have an adequate understanding of the legal basis underlying the transfer of authority, including the difference between delegation and mandate. Nurses also tend to assume that doctors are the parties who are ultimately responsible for the medical actions that have been delegated. Furthermore, the process of delegation of authority is mostly done verbally without adequate documentation. Thus, it is hoped that there will be efforts to increase the understanding of health workers regarding the legal aspects and responsibilities in the delegation of authority through several strategies, including active socialization of regulations and training in the field of health law in the hospital environment.